STRATEGI INSPEKTORAT PEMERINTAH KOTA PROBOLINGGO DALAM MEREALISASIKAN INOVASI KLINIK SULTAN (KLINIK KONSULTASI DAN PENGADUAN) SEBAGAI UPAYA MENINGKATKAN KUALITAS PENGAWASAN APARATUR SIPIL NEGARA (ASN) - Veronica Sri Astuti; Husni Mubaroq; Ega Fitri Qur’aini (Bajang Institute, 2023)
E-sultan was born from a demand for an increase in the quality of supervision to utilize information technology. The use of information technology is intended to increase effectiveness and efficiency in the field of supervision. All State Civil Apparatus (ASN) in Probolinggo City are required to access applications to facilitate their work. With this application all information from each State Civil Apparatus (ASN) will be stored properly. The problem that is considered the most significant in implementing the E-Sultan application is the ability of human resources and technology which sometimes is still unable to handle simple problems. This application is used by the State Civil Apparatus (ASN) in Probolinggo City to make it easier to consult filing. The purpose of this study is to find out how the Inspectorate's strategy is in realizing E-sultan innovation as an effort to improve the quality of supervision of the Probolinggo Municipal Government's State Civil Apparatus (ASN). case study at the City Inspectorate of Probolinggo. This research was carried out at the Inspectorate of the City of Probolinggo and this type of research used descriptive qualitative. Data collection was carried out through field research which included observation, interviews, and documentation. The resource persons in this study consisted of all ASNs at the Inspectorate and several OPD in Probolinggo City. The results of the research are that we can analyze the Inspectorate strategy that has been widely used by Probolinggo City Civil Servants. The focus point of the research is the Probolinggo City Government Inspectorate Strategy in Realizing the Sultan's Clinical Innovation (Consultation and Complaint Clinic) as an Effort to Improve the Quality of State Civil Apparatus (ASN) Supervision.